The role of layered silicate loadings and their dispersion states on the gas separation performance of mixed matrix membrane - Abdul Karim, Zulhairun (Elsevier B. V., 2014)
Mixed matrix membranes (MMMs) embodying different types of organoclays, namely Cloisite® 5, Cloisite® 15A and Cloisite® 30B as the disperse phase for gas separation membranes, were prepared. Polysulfone (PSF) has been used as host matrix to prepare asymmetric membranes attained by the dry-wet phase inversion casting process. FESEM analysis has revealed that defect-free asymmetric MMM morphology with no issues pertaining to non-ideal organic-inorganic interphase was fabricated. The effects of organoclay types and loadings on gas permeation properties were characterized by constant pressure and the variable volume method. From the gas permeation experiment, all nanocomposites exhibited significant reduction in the gas permeation rate even with the addition of very low clay loadings (less than 1wt%). The results suggested that the clay particle loading dictated the extent at which the organoclays were dispersed in the polymer matrix as well as their gas discrimination ability. The information on the degree of clay dispersion, aspect ratio, and the number of clay stacks per tactoid unit was gleaned by making use of the famous phenomenological models derived by Nielsen and Cussler[U+05F3]s group. PSF-C15A membranes with the loading of 0.05wt% were found to be comprised of exfoliated clay nanoplatelet (confirmed by XRD and TEM analysis) with calculated aspect ratio of more than 500 giving rise to striking selectivity (CO2/CH4 ideal selectivity=52.67 for PSF-C15A0.05) well above the recognized intrinsic selectivity for PSF membrane.